Pēteris Elksnītis (1879–1963) – One of The Founders of Dairy Farming in Latvia - Zvirgzdiņš, Indulis (History of Engineering Sciences and Institutions of Higher Education, 2024)
In the interwar period, an important sector of the national economy in Latvia was dairy farming, where both university graduates – engineers, and people without higher education worked. One of them – Pēteris Elksnītis (1879–1963), who learned the trade of a blacksmith in his youth and the trade of a technician through self-learning (1910), worked in the company of the Society of Riga Agricultural Central Union «Konsums», participated in establishing dairies, worked in the Department of Agriculture of the Ministry of Agriculture of the Republic of Latvia where he was responsible for agricultural technique, in the Technical Department of the Central Union of Dairy Farmers of Latvia where he was a Manager, participating in the construction and mechanization of dairies and in setting up milk processing points. In the interwar period, P. Elksnītis not only developed the projects of dairies and creameries and took care of their equipment but also obtained several patents for his inventions for milk processing equipment, potato harvesting, and laundry washing. Some patents related to dairy farming were bought and realized by entrepreneurs in Denmark. After an accident (1932), P. Elksnītis retired from paid work and returned to his home in Prauliena. In 1932, P. Elksnītis was awarded the highest award of the Latvian state – the Order of Three Stars.